DIGITAL ENGLISH TEXTBOOK TO PROMOTE LEARNER AUTONOMY: Student's Need Analysis At Junior High School Padang - Putri, Aprian Dwi; Yulmiati, Yulmiati; Melvina, Melvina Melvina (Universitas Islam Nahdlatul Ulama Jepara, 2025)
The need for the availability of online and digital textbooks in language teaching and learning in the digital age is very considerable. To design and develop a digital textbook, teachers should consider all students’ needs. This study aimed to investigate and explore students’ English necessities, lacks, wants, learner’s motivation, way to prefer learning, available resources, time and place, and learner personal information in 8th grade. This study adopted a qualitative descriptive approach, utilizing a questionnaire and interview as the research instrument. The method of collecting data in this research was carried out by distributing questionnaires to students of class VIII in Junior High School in Padang. The result of the questionnaire average of the students need percentage indicate 72% with high category. Then, the researchers interviewed some students which was chosen the interviewing students by the result of the questionnaire. The result of this research indicates if the students need the digital English textbook that colorful, have more pictures, have audio and videos so they can increase their listening skill to promote their autonomy, especially in increasing and satisfying their curiosity in learning English.